Electricity. Principles and applications - FOWLER, Richard J (McGraw - Hill Book Company, 2003)
Part of the Basic Skills in Electricity and Electronics Series, Electricity makes the introduction to this discipline easy to understand. The program assumes no previous training in the subject; only arithmetic and an introduction to algebra are used in explanations and problems. The text begins with a coverage of the fundamentals of direct current. This leads to a unified presentation of subject generally associated with alternating currents. Throughout the text, concepts build from one chapter to another. This important feature enables students to develop a unified understanding of electricity and the applications of electricity. A dedication to student learning is evident throughout the text. Every page features a vertical color bar that focuses on key words. Many illustrations with a unique four-color design highlight the most important elements. Short self-tests (with answers provided) are presented throughout the text to offer immediate reinforcement and build students' confidence. Another valuable feature is the summary of key concepts found at the end of each chapter. This new edition also includes performance objectives and critical-thinking questions for every chapter.